Introduction to Focus Section: Out in the World: Geography's Complex Relationship with Civic Engagement. Issue 2 (3rd April 2018) - Barcus, Holly R.; Trudeau, Dan
Abstract : Geographers have long been at the forefront of participating in and exploring the intersection of geographic knowledge and community-engaged research. This Focus Section highlights key debates and challenges facing geographers who participate in community-engaged work, explorations of pedagogical and ethical practices, departmental and institutional challenges, and examples of thoughtful applications of geographic knowledge to community-based work. It also seeks to generate knowledge and discussion of how geographers can employ civic engagement to advance geographic learning and enhance the profile of the discipline within and beyond higher education institutions. By focusing on such issues, this collection of articles contributes in vital ways to meet the challenges that higher education institutions face in demonstrating the relevance of academic learning to societal issues. This introduction to the Focus Section reviews the historical context of civic engagement in geography, provides a broad-scale look at the state of civically engaged research in U.S. institutions of higher learning, and highlights the contributions of each of the individual articles included in this Focus Section.